Potential Control of Listeria monocytogenes by Bacteriocinogenic Enterococcus hirae ST57ACC and Pediococcus pentosaceus ST65ACC Strains Isolated From Artisanal Cheese - Cavicchioli, Valéria Quintana; Camargo, Anderson Carlos; Todorov, Svetoslav Dimitrov; Nero, Luís Augusto (Probiotics and Antimicrobial Proteins, 2019)
Bacteriocinogenic Enterococcus hirae ST57ACC and Pediococcus pentosaceus ST65ACC strains, previously isolated from artisanal cheese, were evaluated for their safety with the aim to determine whether they could be used as beneficial strains, especially in the control of Listeria monocytogenes. Both isolates survived simulated gastrointestinal conditions and showed high levels of auto- and co-aggregation with L. monocytogenes, although the hydrophobicity of cells varied. Using the agar-spot test with 33 commercial drugs from different groups, only anti-inflammatory drugs and drugs containing loratadine and propranolol hydrochloride were able to affect the growth of the tested strains. Both strains were resistant to 3 out of 11 antibiotics tested by the disc diffusion method, and low frequencies of antibiotic resistance-encoding genes were observed by PCR analysis. Tested strains neither presented biogenic amine-related genes nor produced these substances. Aside from some antibiotic resistance characteristics, the tested strains were considered safe as they lack other virulence-related genes. E. hirae ST57ACC and P. pentosaceus ST65ACC both presented beneficial properties, particularly their ability to survive gastrointestinal conditions and to aggregate with L. monocytogenes, which can facilitate the elimination of this pathogen. Further studies should be conducted to better understand these interactions.
Keywords: Antibiotic resistance; Beneficial strains; Bacteriocins; LAB; Listeria monocytogenes